Conceptual bases of codification of the legislation in road transport sphere - Довженко, Євгенія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article contains a study of the necessity and prospects of codification of the national Road transport legislation in Ukraine and foreign experience of its implementation. Review of existing studies on the general theoretical issues of codification, and also about problems and prospects of improvement of Ukrainian road transport legislation, allowed to develop a special questions codification of legislation in the field of road transport. For this purpose this article analyzes the existing legislation of road transport, as well as amendments to it, which were proposed in 2013. The author presents his own vision of the conceptual foundations of codifying legislation on road transport. On the basis of this analysis is formulated the conclusion that the legislation in the motor transport sphere needs further improvement. The author expresses opinion, that codification can become the optimum form of perfection of the legislation in area of motor transport, as well as offers structure of the future Code about motor transport of Ukraine